AeU's Innovative Online MBA degree - New, Sarawak Tribune (New Sarawak Tribune, 2019)
The Master Business Administration (MBA) degree is one of the most innovative post-graduate business programme available. Asia e University's (AeU) MBA degree is an internationally benchmarked and recognised qualification.